2017
DOI: 10.14202/vetworld.2017.467-476
|View full text |Cite
|
Sign up to set email alerts
|

Relative gene expression of fatty acid synthesis genes at 60 days postpartum in bovine mammary epithelial cells of Surti and Jafarabadi buffaloes

Abstract: Aim:Aim of the study was to study the relative gene expression of genes associated with fatty acid synthesis at 60 days postpartum (pp) in bovine mammary epithelial cells (MECs) of Surti and Jafarabadi buffaloes.Materials and Methods:A total of 10 healthy Surti and Jafarabadi buffaloes of each breed were selected at random from Livestock Research Station, Navsari and Cattle Breeding Farm, Junagadh, Gujarat, respectively, for this study. Milk sample was collected from each selected buffalo at day 60 pp from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…According to our data, LPL gene expression is highest in Egyptian Buffalo compared to the two HF breeds specially at early lactation stage compared to peak stage. These findings were consistent with those of M Janmeda, V Kharadi, G Pandya, B Brahmkshtri, U Ramani and K Tyagi [ 43 ], who found that, in Surti buffalo, LPL expression was highest on 15th day after calving, then decreased till day 60. Non-esterified free Fatty acids (NEFA) and lipoproteins supply long chain fatty acids (LCFA) to mammary cells, this may explain why the LPL gene is expressed at a higher level during early lactation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our data, LPL gene expression is highest in Egyptian Buffalo compared to the two HF breeds specially at early lactation stage compared to peak stage. These findings were consistent with those of M Janmeda, V Kharadi, G Pandya, B Brahmkshtri, U Ramani and K Tyagi [ 43 ], who found that, in Surti buffalo, LPL expression was highest on 15th day after calving, then decreased till day 60. Non-esterified free Fatty acids (NEFA) and lipoproteins supply long chain fatty acids (LCFA) to mammary cells, this may explain why the LPL gene is expressed at a higher level during early lactation.…”
Section: Discussionsupporting
confidence: 90%
“…As well as, E Sandri, K Harvatine and D Oliveira [ 20 ] found that LPL gene expression in Holstein cattle was highest during the peak [DIM = 60 days] stage of lactation and subsequently dropped during the late stage of lactation. Jaffarabadi buffalo, on the other hand, showed no variation in LPL expression between days 15 and 60 of lactation (M Janmeda, V Kharadi, G Pandya, B Brahmkshtri, U Ramani and K Tyagi [ 43 ]. Similarities between the lactation curve and LPL expression suggest a potential role for this gene in sustaining milk synthesis.…”
Section: Discussionmentioning
confidence: 99%